Influence of Association Network Properties and Ecological Assembly of the Foliar Fugal Community on Crop Quality - Xing, Lei; Zhi, Qiqi; Hu, Xi; Liu, Lulu; Xu, Heng; Zhou, Ting; Yin, Huaqun; Yi, Zhenxie; Li, Juan (Frontiers in Microbiology, 2022)
Revealing community assembly and their impacts on ecosystem service is a core issue in microbial ecology. However, what ecological factors play dominant roles in phyllosphere fungal community assembly and how they link to crop quality are largely unknown. Here, we applied ITS high-throughput sequencing to investigate foliar fungal community assembly across three cultivars of a Solanaceae crop (tobacco) and two planting regions with different climatic conditions. Network analyses were employed to reveal the pattern in foliar fungal co-occurrence, and phylogenetic null model analysis was used to elucidate the ecological assembly of foliar fungal communities. We found that the sensory quality of crop leaves and the composition of foliar fungal community varied significantly across planting regions and cultivars. In Guangcun (GC), a region with relatively high humidity and low precipitation, there was a higher diversity and more unique fungal species, than the region of Wuzhishan (WZS). Further, we found that the association network of foliar fungal communities in GC was more complex than that in WZS, and the network properties were closely related to the sensory quality of crop. Finally, the results of the phylogenetic analyses show that the assembly of the foliar fungal community in GC and WZS was affected by local species diversity and spatial turnover, moreover the assembly further affect the sensory quality of crop leaves. Taken together, our results highlight that climatic conditions and plant cultivars play key roles in the assembly of foliar fungal communities and crop quality, which enhances our understanding of the connections between the phyllosphere microbiome and ecosystem services, especially in agricultural production.